Cervical Primitive Neuroectodermal Tumor in an Adult: Case Report and Literature Review - Alencar, Guilherme dos Santos de; Lucca, Maria Eduarda Turczyn De; Mazzo, Felipe Antonio Torres; Konozoe, Milena Massumi; Jaouhari, Eduardo Talib Bacchi; Morais, Rodrigo Leite de; Barcelos, Carlos Eliseu; Torres, Rosângela Stadnick Lauth de Almeida (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Introduction Primitive neuroectodermal tumors are rare neoplasms of the central nervous system that occur in children, with few reports in adults. These tumors are found most often in the cerebral hemispheres, with spinal cord disorders being rare.Case Report A 71-year-old man with motor and sensory deficits in the upper limbs, cervical pain, and urinary incontinence presented to the Neurosurgery Service. The physical examination revealed grade-III motor strength on the right side, grade IV- on the left upper limb, and grade IV+ on the left lower limb. A magnetic resonance imaging scan showed an expansive intramedullary lesion with a C3-C4 epicenter. Spinal decompression, lesional biopsy, and adjuvant radiotherapy were performed. The anatomopathological report showed a primitive neuroectodermal tumor. After a new treatment with adjuvant radiotherapy (20 × 1.8 Gy in the skull and neuroaxis and 5 × 1.8 Gy in tumor boost), the patient progressed without recurrence.Conclusion Since the characteristics of the tumor are similar to those of medulloblastoma, it is necessary to expand the studies on these lesions, to better understand their pathophysiology and list better diagnostic and therapeutic methods, in addition to those already available.
Keywords: primitive neuroectodermal tumors; adult; medulloblastoma